Avaliações agronômicas de sorgo sacarino para produção de etanol no semiárido: maturação e respostas ao silício - Lessa, Bruno França da Trindade (2016)
The objective of this study was to evaluate the agronomic and technological characteristics of sweet sorghum (Sorghum bicolor (L.) Moench) produced in semiarid as a function the physiological maturity and Silicon fertilization. Was conducted a field experiment in the city of Pentecost - CE with three genotypes (BRS 506, BRS 511 and hybrid 7C30), potassium silicate dosages (0,. 500; 1000 and 1500 mL ha-1) and harvest times, both the stalk cut (90, 97, 104 and 111 days after planting) and for seed harvest (30, 37, 47 and 51 days after full bloom). Was accomplished the production of fresh and dry weight (leaves, stems and panicles), Yield and biochemistry analysis of stalk juice and seed quality. The data were submitted to statistical analysis, normality and homogeneity tests, nonparametric Kruskal-Wallis test for non-normal data, analysis of variance (ANAVA), mean comparison test (Tukey) and polynomial regression to normal or normalized data (Box-Cox system). Average productivity values (total biomass) were 58.6; 64.9 and 24.5 t ha-1 for BRS 506, BRS 511, and hybrid 7C30, respectively, in 2014. In 2015 there was 8.5% decrease for BRS 506 production and 21.2% for BRS 511, but remained at satisfactory levels. In 2014, the varieties achieved yields juice in the order of 20 000 and 22 000 L ha-1, while the hybrid reached only 4000 L ha-1, not being able to ethanol production. The varieties stalks juice showed high standard of biochemical quality 16-18 ºbrix, wherein the BRS 511 showed 157 g L-1 total carbohydrates to 111 days after sowing. In 2015 cultivars maintained high quality stalk juice with total carbohydrates increase (165-167 g L-1). In the 2015 cycle there was effect of silicon fertilizer for the accumulation of dry matter and quality of the stalk juice, increasing the total carbohydrates. The varieties seeds (BRS 506 and BRS 511) showed great physiological conditions (90% germination), reaching the maximum potential vigor after 49 to 53 days after full bloom. The varieties studied (BRS 506 and BRS 511) are recommended for the semiarid region presenting high biomass production and quality stalk juice at 111 days after sowing. Both varieties have a high potential to seeds production with physiological maturity at 113 and 110 days after sowing the varieties BRS 506 and BRS 511, respectively. Finally, 1100 and 1400 ml ha-1 is indicated dosege for the management of sweet sorghum in the semiarid.